Health research capacity building in Georgia: a case-based needs assessment - Squires, A.; Chitashvili, T.; Djibuti, M.; Ridge, L.; Chyun, D. (Public health (London), 2017)
Research capacity building in the health sciences in low- and middle-income countries (LMICs) has typically focused on bench-science capacity, but research examining health service delivery and health workforce is equally necessary to determine the best ways to deliver care. The Republic of Georgia, formerly a part of the Soviet Union, has multiple issues within its healthcare system that would benefit from expended research capacity, but the current research environment needs to be explored prior to examining research-focused activities. The purpose of this project was to conduct a needs assessment focused on developing research capacity in the Republic of Georgia with an emphasis on workforce and network development. A case study approach guided by a needs assessment format. We conducted in-country, informal, semi-structured interviews in English with key informants and focus groups with faculty, students, and representatives of local non-governmental organizations. Purposive and snowball sampling approaches were used to recruit participants, with key informant interviews scheduled prior to arrival in country. Documents relevant to research capacity building were also included. Interview results were coded via content analysis. Final results were organized into a SWOT (strengths, weaknesses, opportunities, threat) analysis format, with the report shared with participants. There is widespread interest among students and faculty in Georgia around building research capacity. Lack of funding was identified by many informants as a barrier to research. Many critical research skills, such as proposal development, qualitative research skills, and statistical analysis, were reported as very limited. Participants expressed concerns about the ethics of research, with some suggesting that research is undertaken to punish or ‘expose’ subjects. However, students and faculty are highly motivated to improve their skills, are open to a variety of learning modalities, and have research priorities aligned with Georgian health needs. This study's findings indicate that while the Georgian research infrastructure needs further development, Georgian students and faculty are eager to supplement its gaps by improving their own skills. These findings are consistent with those seen in other developing country contexts. •Key informants detail health research landscape in Republic of Georgia.•Strengths include: committed faculty and lots of collaborative experience.•Weaknesses include: funding, limited knowledge of statistics, and research design.•Findings are organized into SWOT analysis and contextualized.•Relevant policy recommendations are made and skill priorities identified.